ASIMILASI ISLAM DENGAN BUDAYA LOKAL DI NUSANTARA - Mukhlishin, Ahmad; Jamil, Muhammad; Maba, Aprezo Pardodi (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Islam as a religion that is present in all tribes in the archipelago as a value system that integrates with the local culture, so this is often seen by people outside the tribe with Islam Minangkabau, Javanese Islam, and so on. The accumulation of cultures with various intercourses called multiculturalism. But the great possibility both can play an important role in shaping a new culture, because there is a dialogue between the orders of religious values ​​that become the idealism of a religion with local cultural values. As a system of knowledge, religion is a belief system that is full of moral teachings and guidance of life must be studied, examined and then practiced by man in his life. In this case religion provides clues about the